Development and validation of a simple and sensitive RP-HPLC method for simultaneous estimation of drospirenone and ethinylestradiol in combined tablet dosage form - Warkad, Shrikant D.; Santhakumari, B.; Chandewar, A. V. (International Journal of Pharmacy and Pharmaceutical Sciences, 2012)

Development and validation of a sensitive bioanalytical method for the determination of sumatriptan in rat plasma by UPLC-MS - Kumbhar, Amruta B.; Galgatte, Upendra C.; Warkad, Shrikant D.; Santhakumari, B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2013)

Molecular investigations of protriptyline as a multi-target directed ligand in alzheimer's disease - Bansode, Sneha B.; Jana, Asis K.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Joshi, Rakesh S.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (Plos One, 2014)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving multiple cellular and molecular processes. The discovery of drug molecules capable of targeting multiple factors involved in AD pathogenesis would greatly facilitate in improving therapeutic strategies. The repositioning of existing non-toxic drugs could dramatically reduce the time and costs involved in developmental and clinical trial stages. In this study, preliminary screening of 140 FDA approved nervous system drugs by docking suggested the viability of the tricyclic group of antidepressants against three major AD targets, viz. Acetylcholinesterase (AChE), beta-secretase (BACE-1), and amyloid beta (A beta) aggregation, with one member, protriptyline, showing highest inhibitory activity. Detailed biophysical assays, together with isothermal calorimetry, fluorescence quenching experiments, kinetic studies and atomic force microscopy established the strong inhibitory activity of protriptyline against all three major targets. The molecular basis of inhibition was supported with comprehensive molecular dynamics simulations. Further, the drug inhibited glycation induced amyloid aggregation, another important causal factor in AD progression. This study has led to the discovery of protriptyline as a potent multi target directed ligand and established its viability as a promising candidate for AD treatment.

Tolbutamide induces conformational change and promotes albumin glycation - Bansode, Sneha B.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Jana, Asis K.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2015)
Tolbutamide is a first generation sulfonylurea drug used for the treatment of type II diabetes. In the present study, the effect of tolbutamide on albumin conformation was investigated using BSA as a model protein. The binding of tolbutamide induced a conformational change in albumin, which was confirmed by thioflavin T assay, ANS assay, and CD spectroscopy. Computer simulations suggested that the binding of tolbutamide increases the solvent accessibility of lysine residues, the hotspots of glycation. Furthermore, the change in conformation of albumin facilitates increased glycation, which was observed by AGE specific fluorescence and the results were corroborated by mass spectrometric analysis. This study suggested that tolbutamide enhances albumin glycation by inducing conformational change in BSA and hence could be a potential risk factor if used for a prolonged period.

Investigation of the biocompatibility and cytotoxicity associated with ROP initiator and its role in bulk polymerization of L-lactide - Parwe, Sharad P.; Warkad, Shrikant D.; Mane, Manoj V.; Shedage, Pranita S.; Garnaik, Baijayantimala (Polymer, 2017)
Poly (L-lactide) (PLLA) is one of the most attractive polymers for use in biomedical applications. In such applications it is necessary to reduce the use of toxic chemicals and catalysts used in PLLA synthesis, to minimize any adverse effects. In view of this, we have performed ring opening polymerization (ROP) of Llactide (LA) using biocompatible initiator, namely, Zinc L-Proline (ZnP) in bulk. High molecular weight PLLA (Mw up to 1.45 x 10(5) Da) was obtained using the ZnP complex. The ZnP complex is safe, easy to prepare, store and handle. H-1 and C-13 NMR spectra of PLLA were used to determine the extent of monomer conversion and stereo sequence respectively. Differential Scanning Calorimetry (DSC) and Size Exclusion Chromatography (SEC) were used to determine thermal properties, Mn, Mw and polydispersity index respectively. The mechanism of ROP of LA in the presence of ZnP was studied using Density Functional Theory (DFf) which was in good agreement with results from H-1 NMR and Matrix-Assisted Laser Desorption/Ionization Spectrometry (MALDI-TOF). Biocompatibility/non toxicity of PLLA prepared using ZnP was studied in-vitro using MTT assay by examining the proliferation rate of mouse myoblast C2C12 cell line. Escherichia coli and Staphylococcus aureus were used for the study of antibacterial activity of PLLA. (C) 2017 Elsevier Ltd. All rights reserved.